Biliary precipitation during ceftriaxone therapy: frequency and risk factors - (:unkn) unknown (TURKISH J PEDIATRICS, 2007)
Ceftriaxone, a third-generation cephalosporin, is widely used for treating infection during childhood. It is mainly eliminated in the urine, but approximately 40% of a given dose is unmetabolized and secreted into bile. The aim of this study was to investigate the frequency, clinical characteristics, and outcome of biliary sludge (BS) in addition to potential contributing risk factors in children who receive ceftriaxone. Biliary ultrasonography was performed at the time of randomization before ceftriaxone treatment was started, on the 5th and 10(th) days, and at the end of the treatment. If BS was detected, patients were followed-up weekly by sonographic examination until the BS or biliary lithiasis (BL) disappeared. A total of 114 children (56 girls, 58 boys; age range: 2-180 months, mean 47.5 +/- 46.3 mos) were enrolled in the study. Fourteen (12%) subjects developed BS and 10 (9%) developed BL on the 5th day of treatment. On the loth day of treatment, 20 (18%) subjects developed BS and 15 (13%) developed BL. In total, 35 (31%) of all subjects developed biliary precipitation (BP), of whom 20 (57%) were diagnosed as BS and 15 (43%) as BL. All subjects who developed BP were found to be asymptomatic during the course of therapy. Patient age over 12 months, daily total dose of ceftriaxone of more than 2 g, and duration of treatment longer than five days were found to be associated with BP. Ceftriaxone frequently causes transient Bps and its probability increases if the child is over 12 months of age, the dose is over 2 g/day, or the duration is over five days. Neither radiologic investigation nor the discontinuation of treatment with ceftriaxone is necessary as long as the patient is asymptomatic.
Keywords: ceftriaxone therapy; biliary precipitation; biliary sludge; GALLBLADDER SLUDGE; PSEUDOLITHIASIS; LITHIASIS; CHILDREN